2022
DOI: 10.34133/2022/9817134
|View full text |Cite
|
Sign up to set email alerts
|

Direct Retrieval of NO 2 Vertical Columns from UV-Vis (390-495 nm) Spectral Radiances Using a Neural Network

Abstract: Satellite retrievals of columnar nitrogen dioxide (NO2) are essential for the characterization of nitrogen oxides (NOx) processes and impacts. The requirements of modeled a priori profiles present an outstanding bottleneck in operational satellite NO2 retrievals. In this work, we instead use neural network (NN) models trained from over 360,000 radiative transfer (RT) simulations to translate satellite radiances across 390-495 nm to total NO2 vertical column (NO2C). Despite the wide variability of the many inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 101 publications
2
5
0
Order By: Relevance
“…For example, the range 400-500 nm slightly degrades the results, while further reducing the range to 400-470 nm leads to a bit more degradation. This is consistent with the full spectral resolution results of Li et al (2022) who found an optional retrieval window of 390-495 nm for estimating NO 2 vertical columns. Our results indicate that most of the information for NO 2 at OCI spectral resolution is provided by the high frequency structure of the radiances produced by NO 2 absorption within the fitting window currently used in the OMNO2 product.…”
Section: Results With Simulated Pace Oci Spectrasupporting
confidence: 91%
See 2 more Smart Citations
“…For example, the range 400-500 nm slightly degrades the results, while further reducing the range to 400-470 nm leads to a bit more degradation. This is consistent with the full spectral resolution results of Li et al (2022) who found an optional retrieval window of 390-495 nm for estimating NO 2 vertical columns. Our results indicate that most of the information for NO 2 at OCI spectral resolution is provided by the high frequency structure of the radiances produced by NO 2 absorption within the fitting window currently used in the OMNO2 product.…”
Section: Results With Simulated Pace Oci Spectrasupporting
confidence: 91%
“…Spectral fitting algorithms can be computationally intensive and it may still be desirable to use machine learning to speed up the processing of dense imager data as shown in Figure 8. For example, Li et al (2022) found that a NN implementation for NO 2 vertical columns using TROPOMI spectra was about 12 times faster than a full implementation using a priori profiles from a high spatial resolution chemistry-transport model.…”
Section: Practical Implementation Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithm efficiency is particularly important for current and future atmospheric composition instruments, including those in geostationary orbit, that have very large data volumes. Machine learning has been shown to be an efficient means of estimating NO 2 vertical columns from satellite spectra (Li et al, 2022) as well as for other applications in remote sensing and geoscience (Maxwell et al, 2018;Lary et al, 2016). In addition, machine learning combined with principal component analysis may be able to reduce noise in the spectral fitting compared with the more traditional approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of characterizing the free tropospheric NO2 background was brought to the fore by the use of OMI NO2 data to infer NOx emission trends in the contiguous United States (CONUS) (Jiang et al, 2018;Silvern et al, 2019;Qu et al, 2021;He et al, 2022;Jiang et al, 2022). The OMI NO2 data over CONUS show a steady decrease from 2005 to 2009 (Russell et al, 2012;Duncan et al, 2013;Duncan et al, 2016;Krotkov et al, 2016), consistent with the decreases of NOx emissions reported in the EPA National Emission Inventory (NEI), but Jiang et al (2018) found that the trend flattened after 2009 despite sustained decreases in NOx emissions according to the NEI and supported by NO2 surface data (Silvern et al, 2019).…”
mentioning
confidence: 99%